Enhancing Clinical Data Reliability through Predictive Machine Learning-Driven Intelligent DevOps Frameworks (International Journal of Research Publications in Engineering, Technology and Management (IJRPETM), 2025)
The rapid digitization of healthcare systems has generated enormous volumes of clinical data from electronic health records, medical imaging systems, wearable devices, laboratory platforms, and healthcare information networks. Ensuring the reliability, accuracy, availability, and security of this data has become a critical challenge for healthcare organizations. Traditional approaches to clinical data management often struggle with data inconsistencies, system failures, delayed error detection, and difficulties in maintaining continuous integration across complex healthcare environments. Predictive machine learning-driven intelligent DevOps frameworks provide an advanced solution by combining artificial intelligence, automation, continuous monitoring, and adaptive operational practices to enhance clinical data reliability. These frameworks utilize machine learning algorithms to predict potential data quality issues, detect anomalies, optimize system performance, and automate corrective actions before failures affect healthcare operations. The integration of DevOps principles with predictive analytics enables seamless collaboration between development, operations, and clinical technology teams while improving scalability and resilience. This research explores the role of intelligent DevOps frameworks in strengthening clinical data reliability through predictive machine learning techniques. It examines architectural approaches, data governance mechanisms, automation strategies, and predictive models that support reliable healthcare information systems. The study proposes a methodological framework for evaluating the effectiveness of machine learning-enhanced DevOps environments in improving clinical data integrity, operational efficiency, and patient-centered healthcare outcomes
Keywords: Clinical data reliability; predictive machine learning; intelligent DevOps; healthcare information systems; artificial intelligence; data quality management; continuous integration; anomaly detection; healthcare automation; predictive analytics